ETHICS IN FINANCIAL REPORTING AND ORGANIZATIONAL COMMUNICATION - Maria Daniela BONDOC; Marian TAICU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2019)
The subject of ethics have been intensely debated in the economic literature because of its impact on information users' decisions. In the process of preparing financial reports, it is necessary to respect ethical principles for the defense of the public interest. An unethical organizational reporting can cause problems throughout the economy by affecting the confidence of the stakeholders. Respecting ethics in organizational communication, including financial reporting, is often questioned by stakeholders. If investors are confident that the principles of ethics in financial reporting and organizational communication have been respected, they can invest more, thus contributing to the development of the entire economy. The main objective of our paper is to highlight the imperative character of observing ethical principles in financial reporting and organizational communication.